(The Study of Making ceiling from Compound of Fly ash, Bottom ash, cement and Short Cocnut Fibre and Techno-economic Analysis) - H G Pohan; Ade Suherman (Balai Besar Industri Agro, 2007)
The research of making ceiling from mixture of main component (fly ash,and bottom ash)with cement and short of coir fibre have been conducted. The treatment consist of the amount of component, cement and short of coir and fibre size. The caracteristic of ceiling to be analyzed as according to national standar of Indonesia SNI No.0233-1989 consist of: external profile, specific gravity, size measure, compactness, strong flex, ability nailed, wight fill, and water absorbtion. The results show that ceiling produced has difference between ceiling from the fly ash and bottom ash. From the both of main component seen that surface of ceiling are same burst and streng flex still lower. The strong flex from fly ash between 18,4-24,5 kg/cm3,specific gravity between 1,47-1,65 g/cm3 and water absorbtion between 15,95-19,7%, while from bottom ash the strong flex between 11,2-23,2 kg/cm3, specific gravity between 1,52-1,63 g/cm3 and water absorbtion between 16,25-20,58%. The analysis of tehno-economic indicate that cost of goods manufactured equal to Rp780,-/ceiling. At the price of selling Rp1.300,-/ceiling,hence return of investment during 2,5 year with the totally of invesment equal to Rp 19.500.000.